Textile Art from Mixed-Media on the Struggles of Kayayie in Ghana - Edem Kwami, Buami; Tsotorvor, Rejoice Makafui; Akuoko Adjei, Daniel Akuoko; Ahiabor, Robert; Howard, Ebenezer Kofi (Journal of Urban Culture Research, 2024)
Kayayie is the name of a leading portering activity by young Ghanian girls making a living assisting people in transporting their goods from crowded market spaces and bus stations. These girls are under stress and the challenges being on the street. This study employed mixed-media and textile art with a studio-based design approach to effectively carry out the project highlighting their plight. The motivation is to showcase their struggles with their loads in making a living. It was revealed that accommodations remained a major problem facing these female porters as they tend to sleep in front of kiosks, lorry stations or other places along the street. Due to this, some are raped and give birth to fatherless children as they become single parents at a tender age. The creation of textile art pieces serves as a skill-based trade to generate income for their well-being and promote creative artistic development. The artistic process incorporates various techniques, including applique (both sewing and gluing), yarn doodling and others Further experiments of the various adhesives reveal that some adhesives such as super glue, super adhesive glue, fevicol SH has a very high cohesion bond with the materials and dries faster thereby improving production, while some adhesives do not bond well with certain materials.